Tecken på liv - Stehn, Ilona (2008)
The City is filled with signs of life. It teems with human traces waiting to be discovered. Street art of different kinds prevails behind traffic signs, on posts and electrical boxes. Personally con-structed dogs guard roundabouts all around Sweden and small gardens spire underneath window ledges. In this work I want to identify these phenomena and find out what thoughts inspired these creations. My focus has been to interview creators I believe have wanted to contribute something positive to the city life. I call these expressions creative imprints.